Post-combustion absorption carbon capture assisted by sorption-compression cascade heat pump - Y. Huang; W. Liu; Y.X. Zhang; X.J. Zhang; T. Wang; M.X. Fang; Y.L. Yao; X. Zheng; X.Y. Liu; L. Jiang (Carbon Capture Science & Technology)
The application of heat pumps in carbon capture systems is crucial for post-combustion carbon capture in power plants. However, existing heat pump and carbon capture coupling schemes face issues such as excessive electricity consumption or low waste heat recovery efficiency. Therefore, energy-saving processes are equally indispensable for reducing the energy consumption of carbon capture. A novel cascade heat pump, that is composed of absorption heat pump and lean vapor recompression, is initially proposed for amine-scrubbing capture system. Based on different waste heat utilization and heat pumps, various energy-saving processes are evaluated based on an absorption carbon capture system for a 660 MW coal-fired power plant. The results indicate that the cascade heat pump type is conducive to reducing energy consumption, while the single-stage type results in lower power efficiency loss. At a 90 % carbon recovery rate, the optimal unit energy consumption of the capture system is 2.23 GJ/tCO2, which is achieved by cascade heat pump coupling with additional steam extraction for generator at flash pressure of 40 kPa. The minimum efficiency loss of power plant is 7.5 % by using lean vapor recompression with waste heat utilization in reboiler and flash drum at flash pressure of 80 kPa and 100 kPa. The maximum net CO2 recovery rate of 73.48 % is achieved by using lean vapor recompression with waste heat utilization in reboiler and flash drum at flash pressure of 80 kPa. The comparative results pose a great potential considering the cascade heat pump for power plant in the future.